ABORTION IN INDONESIA ON POSITIVE LAW AND MASLAHAH THEORY PERSPECTIVE - Sakti, Rindy Kumala; Shodiq, Ja'far; Isnaini, Enik (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
Abortion is a social phenomenon that is increasingly concerning, this study seeks to answer the question, how the legal regulation of abortion in Indonesian positive law and how the analysis of maslahah against abortion. This research is a normative legal research using statutory approach and conceptual approach, namely the theory of maslahat. The results concluded, first; the act of abortion is prohibited and threatened with criminal penalties as mentioned in articles 299, 346, 347, 348 and 349 of the Criminal Code. However, under certain conditions, such as medical emergencies, abortion is allowed. This is mentioned in articles 31, 32, 33 and 34 of Government Regulation (PP) No. 61/2014 on Reproductive Health. Second, the prohibition and permissibility of abortion is in line with maslahat theory, abortion is prohibited because it can cause damage and abortion is allowed due to emergency conditions.